Epidemiologia e fatores de risco associados à colonização por VRE e MRSA em uma unidade de terapia intensiva de adultos - Batistão, Deivid William da Fonseca (2010)
This investigation included a total of 78 VRE-colonized patients and 17 MRSA-colonized patients through study of the incidence in the period April 2009 to January 2010. We evaluated the rates of infection/colonization with these phenotypes, risk factors for colonization, antimicrobial susceptibility profile and characterization of vanA gene in enterococci strains with high level vancomycin resistance. The identification of S. aureus and enterococci species was performed by conventional biochemical tests. The vancomycin minimal inhibitory concentration (MIC) was evaluated by E-test method. The antimicrobial susceptibility profile and high level aminoglycoside resistance were carried out by discdiffusion. To assess the genotype enterococcal strains expressing high-level vancomycin resistance, we used the polymerase chain reaction. Epidemiological data were recorded for all patients included in the study and were used for the risk factor analysis. A case-control study was then performed. The cases were defined as only patients with VRE colonization (n=21), and the controls were those without VRE colonization or infection from any organism (n=143). A total of 333 patients hospitalized were enrolled in this investigation. Of the 90 patients colonized with Enterococcus spp., 92 samples were isolated. Seventy seven patients (23.1%) were colonized with VanC VRE and only one patient (0.3%) with VanA-type. Four of 92 samples were identified as Enterococcus faecium, 11 as Enterococcus faecalis, 26 as Enterococcus gallinarum and 51 as Enterococcus casseliflavus. The risk factors that were determined through univariate analysis to be significantly associated with VRE colonization included nephropathy, diabetes mellitus, prior ICU antibiotic use, vancomycin and carbapenem use in the ICU. In the multivariate analysis, significant independent risk factors for VRE colonization were the nephropathy (P < 0.001), prior ICU antibiotic use (P = 0.03) and carbapenem use (P < 0.001). Our investigation revealed a low frequency of MRSA colonization (5.1%) with 23.5% of colonized patients progressed to infection by this organism (P <0.001, OR = 32.1), especially for cases of sepsis (P = 0.01, OR = 20.9). VRE colonization, particularly the VanC phenotype, was frequent in the ICU and although of little clinical importance, these microorganisms are considered reservoirs of resistance genes. There was a correlation between the vancomycin and carbapenems use and VRE colonization, although the results of multivariate analysis did not demonstrate vancomycin as an independent risk factor for VRE colonization. We found a low incidence of MRSA in the ICU and observed a significant relationship between colonization and the development of sepsis by this microorganism.